Sedimentary cover and structural trends affecting the groundwater flow in the Nubian Sandstone Aquifer System: Inferences from geophysical, field and geochemical data - Mohamed, Ahmed; Alarifi, Saad S.; Abdelrady, Ahmed (Frontiers in Earth Science, 2023)
This study combined gravity data from the Earth Gravitational Model with borehole data to better understand the spatial variations of the sedimentary cover and the structural trends that affect groundwater flow in the Nubian Sandstone Aquifer System. Our findings were verified and evidenced by geological, geochronological, geochemical data, and earthquake records: (1) the Uweinat-Aswan basement uplift, which runs east-west, partially isolates the deep intracratonic Dakhla Basin from the shallower northern Sudan basin, and thereby impeding the south-to-north groundwater flow from N. Sudan platform to the Dakhla Basin; (2) a thickening of the sedimentary cover in the NE-SW direction from the southern Kufra through the northern Kufra to the Dakhla Basin; (3) The sedimentary cover was found to increase from less than 500 m in the south (Northern Sudan and Uweinat region) to more than 6 km in the north (Mediterranean coast); (4) a number of structural trends (NE-SW, N-S, E-W, and NW-SE) affecting the region; (5) A large Pelusium mega shear system that runs northeast to southwest makes it easier for groundwater to flow from the Kufra Basin to the Dakhla Basin; (6) Along the paths that groundwater takes, like from Siwa to Qattara and from northwest Farafra to north Bahariya, and along structures that run in the same direction as the flow, older 36Cl groundwater ages were observed; (7) It is a better way to learn about the hydrogeological context of large aquifers and figure out how to best manage these underground water sources